1986
DOI: 10.1071/bi9860125
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Spots in the WoolBearing Skin of White Merino Sheep Induced by Ultraviolet Light

Abstract: Black-grey pigmented skin spots, some of which contained pigmented wool fibres, were observed in a flock of 8· 5-year-old white Merino ewes. The spots were concentrated along the backline and increased in number following shearing, suggesting exposure to sunlight to be of importance in the development of these non-congenital pigmented skin spots in genetically white Merino sheep. To test the effect of ultraviolet light, white Merino sheep, ranging in age from 3 to 8 years, had a closely clipped mid side area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Fleet (2006) showed that twice yearly shearing increased the development of pigmented spots after 2 years of treatment. This result, with the agerelated trends observed here, is consistent with the idea that exposure of the skin to ultraviolet light (e.g., following shearing) increases the risk of developing black spots in the fleece area (Forrest & Fleet 1986).…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…Fleet (2006) showed that twice yearly shearing increased the development of pigmented spots after 2 years of treatment. This result, with the agerelated trends observed here, is consistent with the idea that exposure of the skin to ultraviolet light (e.g., following shearing) increases the risk of developing black spots in the fleece area (Forrest & Fleet 1986).…”
Section: Descriptive Statisticssupporting
confidence: 92%
“…Ovine dermis is considerably thicker than human dermis;(Dellmann and Eurell, 1998) in addition a layer of wool equivalent of SPF 30 protection also makes it difficult to assess how much photoageing is induced in these dermal tissue samples as compared with human samples. (Fleet, 2006; Forrest and Fleet, 1986) However given that the Sham and OVX ovine were provided with the same sheltering condition, the effects observed in this study signify change in the hormonal level rather than differential UV radiation exposure.…”
Section: Discussionmentioning
confidence: 73%
“…A series of environmental and genetic factors may be related to the number of spots. Simple observation (even in humans) suggests that this number increases with age and environmental stress factors (e.g., solar irradiation can be invoked as causative agents [7,8,14,23]). Variability in the underlying genetic mechanisms responsible for the spots is likely, at least in different races, as well as in susceptibility to environmental stress factors.…”
Section: Discussionmentioning
confidence: 99%